Beauty ideals and body positivity: a qualitative investigation of young women’s perspectives on social media content in China - Lang, Min; Ye, Yiduo (Frontiers in Psychology, 2024)
Much of the existing knowledge regarding the impact of beauty ideals and body positive social media content on women's body image is based on the Western cultural context. This limits our understanding of the issue in other cultures, such as China, among others. Therefore, to address this gap, this study examined young Chinese women's perspectives on beauty ideals and body positivity in social media through a qualitative investigation. Female university students in China (N=24) participated in individual interviews. A thematic analysis revealed four primary themes: (1) characteristics of mainstream beauty ideals in Chinese social media; (2) impact of beauty ideals on young women; (3) perspectives on the content and roles of body positivity; (4) influences of body positive social media content on young women. These findings indicate that young Chinese women are aware of the beauty ideals in social media and their negative impact on their body image. Furthermore, young Chinese women generally expressed a favorable outlook on body positivity but noted its limitations.